2016
DOI: 10.1523/jneurosci.2394-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory Dynamics Underlie Memory Impairments after Repeated Social Defeat

Abstract: Repeated social defeat (RSD) is a murine stressor that recapitulates key physiological, immunological, and behavioral alterations observed in humans exposed to chronic psychosocial stress. Psychosocial stress promotes prolonged behavioral adaptations that are associated with neuroinflammatory signaling and impaired neuroplasticity. Here, we show that RSD promoted hippocampal neuroinflammatory activation that was characterized by proinflammatory gene expression and by microglia activation and monocyte trafficki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
172
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(185 citation statements)
references
References 55 publications
13
172
0
Order By: Relevance
“…In the RSD model, stress-induced neuroinflammation impaired hippocampal neurogenesis and promoted cognitive and affective behavioral deficits [51]. In this study, mice that were exposed to stress showed transient impairments in spatial memory recall that resolved within 28 days after stress cessation.…”
Section: Stress-induced Neurobiological Dysfunctions Are Associated Wmentioning
confidence: 57%
See 2 more Smart Citations
“…In the RSD model, stress-induced neuroinflammation impaired hippocampal neurogenesis and promoted cognitive and affective behavioral deficits [51]. In this study, mice that were exposed to stress showed transient impairments in spatial memory recall that resolved within 28 days after stress cessation.…”
Section: Stress-induced Neurobiological Dysfunctions Are Associated Wmentioning
confidence: 57%
“…Treatment with minocycline, an antibiotic that has antiinflammatory properties at the periphery and in the brain, prevented microglia activation and abrogated impairment in spatial memory after RSD. Minocycline did not prevent deficits in neurogenesis nor did it prevent the persistence of social avoidance behavior in mice exposed to stress [51]. These findings suggest that neuroinflammatory activation after psychosocial stress impairs spatial memory performance independent of deficits in neurogenesis and social avoidance [51].…”
Section: Stress-induced Neurobiological Dysfunctions Are Associated Wmentioning
confidence: 76%
See 1 more Smart Citation
“…In support of this notion, microglia activation was inhibited by pharmacological treatment with minocycline in a variety of stress models. In each case, inhibiting microglia during stress exposure attenuated the increase of pro-inflammatory cytokines normally produced by stress (Hinwood, Morandini et al 2012, Hinwood, Tynan et al 2013, Kreisel, Frank et al 2014, McKim, Niraula et al 2016). …”
Section: Rsd Activates Stress Circuitry Promotes Neuroinflammation mentioning
confidence: 98%
“…in type 1 and type 2 diabetes [19]. It influences brain function [20], memory [20], appetite [21] [22] and the cognitive response i.e. the ability of the brain to function and is associated with the regulatory and/or causal mechanism rather than the visceral or symptomatic consequences.…”
Section: Discussion Of the Different Factors Which Influence The Onsementioning
confidence: 99%